Strategi Implementasi Manajemen Perubahan dalam Meningkatkan Kinerja Bisnis pada UMKM Perikanan Kabupaten Karawang - Asep Jamaludin; Sihabudin Sihabudin; Yudi Firmansyah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Competition in the business world is indeed very tight in Indonesia, as in many other countries. Indonesia’s economic growth has created new business opportunities, attracting many MSMEs who were born to compete in pursuing a growing market share. The purpose of this study is to determine the implementation strategy of change management in an effort to improve business performance in fishery MSMEs in Karawang Regency. This study observes and analyzes using a descriptive quantitative approach. This study has an “ex-post de facto” nature. The implementation strategy of change management can make a significant contribution to improving business performance. Implementation strategies help organizations to be more responsive to changes in the market environment. This allows businesses to adapt more quickly to new trends and demands, maintaining competitiveness. Focusing on change drives a culture of innovation within the organization. Employees who feel encouraged to provide ideas and try new things can create innovative solutions to improve performance